Dairy productivity and climatic conditions: econometric evidence from South‐eastern United States. (21st November 2012) - Mukherjee, Deep; Bravo‐Ureta, Boris E.; De Vries, Albert
<x xml:space="preserve">Abstract</x> Climate change and food security have become critical issues in the agricultural policy agenda. Although global warming is expected to increase both the frequency and severity of heat stress on dairy cattle, there are very few economic studies focusing on this issue. This paper contributes to the literature by integrating the frontier methodology, commonly used in applied production economics, with heat stress indexes used by animal scientists but largely ignored by economists. Our econometric models are useful to quantify gross benefits expected from adaptation to climatic conditions represented by the Temperature Humidity Index (THI) and alternatively by the Equivalent Temperature Index (ETI). Stochastic production frontier analysis is used to measure technical efficiency for an unbalanced panel of 103 dairy farms located in Florida and Georgia. Five alternative model specifications are evaluated. The results reveal that both THI and ETI have a significant nonlinear negative effect on milk production. The climatic indexes when incorporated in the frontier specification absorb some of the output shortfall that otherwise would be attributable to inefficiency. The results indicate that using fans combined with sprinklers is an effective adaptation to offset output losses stemming from heat stress conditions.